Effects of cattle grub treatment. - Bell, F.W.; Dean, G.A. (Kansas Agricultural Experiment Station, 2012)
Five heifers in each of four lots of 10 head each were treated with rotenone dust December 11, 1945. The other five heifers in each lot received no treatment for grubs. At the time of treatment a careful count was made of the number of grubs on each of the 10 heifers in each lot. Thus the trial furnishes data on 20 heifers treated for grubs and 20 which were not treated, with all factors of feeding and management being the same in each lot. Another check for evidence of any grubs which might not have been killed by the first treatment was made January 9, 1946. On this date all the heifers previously treated which showed any grubs not destroyed were dusted again with rotenone dust. Each lot of heifers was marketed when they averaged about 850 pounds in weight. Since the feeding trial was to determine the results of different quantities of grain fed to finish the cattle, the dates of marketing the four lots ranged from May 31, 1946 to July 30, 1946.
Keywords: Beef; Grub treatment; Rotenone dust; Gain; Carcass gain